Factors predicting secondary hypertension in young adults with hypertension: a retrospective study - Nicha Prasert; Worapaka Manosroi; Benya Hankamolsiri; Muslimah Wae-uma; Papot Choonklai (BMC Cardiovascular Disorders)
Abstract Background Hypertension in young adults is often due to secondary causes, and investigating these can be resource-intensive. This study aimed to identify clinical and biochemical markers that could suggest secondary hypertension in individuals under 40 years. Materials and methods A 6-year retrospective observational cohort study included 207 young adults with hypertension who were assessed for secondary causes such as hyperthyroidism, primary aldosteronism, Cushing’s syndrome, pheochromocytoma, and renovascular disease. Multivariable logistic regression was used to identify significant predictors, with a significance level set at p < 0.05. Results Secondary hypertension was diagnosed in 7 patients (3.4%). The most common diagnoses were primary aldosteronism and hyperthyroidism. Three significant clinical and biochemical predictors were identified: female (OR 4.56, p = 0.020), systolic blood pressure > 160 mmHg at the time of diagnosis (OR 1.44, p = 0.010), and serum potassium < 3.5 mEq/L (OR 3.69, p = 0.019). Conclusion Several easy-to-obtain clinical and biochemical markers can help identify secondary hypertension in young adults. Individuals who do not have any of these predictors may have a lower likelihood of secondary hypertension; however, these markers should always be used in conjunction with a thorough clinical assessment and are not intended to serve as definitive criteria for diagnosis. Clinical trial number Not applicable.